2005
DOI: 10.1073/pnas.0506825102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a hyaluronidase, Hyal5, involved in penetration of mouse sperm through cumulus mass

Abstract: A glycosylphosphatidylinositol (GPI)-anchored hyaluronidase, PH-20, on the sperm surface has long been believed to assist sperm penetration through the cumulus mass surrounding the eggs. However, mouse sperm lacking PH-20 were still capable of penetrating the cumulus mass despite a delayed dispersal of cumulus cells. Intriguingly, a 55-kDa hyaluronan-hydrolyzing protein was abundantly present in wild-type and PH-20-deficient mouse sperm. In this study, we purified the 55-kDa mouse protein from soluble protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
172
4
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(185 citation statements)
references
References 43 publications
7
172
4
2
Order By: Relevance
“…It is the hydrolytic enzymes released following the AR that ensure sperms to disperse the cumulus mass and reach the zona layer (Talbot, 1985;Yanagimachi, 1988). Unfortunately, this hypothesis is challenged by the observation that the expression of hydrolytic enzymes thought to facilitate sperm penetration of the cumulus, PH-20 and Hyal5, were found on the surface of sperm membrane but not within the acrosome (Lin et al, 1994;Kim et al, 2005;Kimura et al, 2009), which means sperm do not necessarily undergo AR to release hydrolytic enzymes when passing through the cumulus layer. Recent results obtained from PH-20 null mice have revealed that mouse sperm lacking PH-20 are still fertile with only delayed penetration through the cumulus (Baba et al, 2002), while sperm lacking both PH-20 and Hyal5 have not yet been studied.…”
Section: Status Of Sperm Acrosome In the Cumulus: The Controversymentioning
confidence: 97%
“…It is the hydrolytic enzymes released following the AR that ensure sperms to disperse the cumulus mass and reach the zona layer (Talbot, 1985;Yanagimachi, 1988). Unfortunately, this hypothesis is challenged by the observation that the expression of hydrolytic enzymes thought to facilitate sperm penetration of the cumulus, PH-20 and Hyal5, were found on the surface of sperm membrane but not within the acrosome (Lin et al, 1994;Kim et al, 2005;Kimura et al, 2009), which means sperm do not necessarily undergo AR to release hydrolytic enzymes when passing through the cumulus layer. Recent results obtained from PH-20 null mice have revealed that mouse sperm lacking PH-20 are still fertile with only delayed penetration through the cumulus (Baba et al, 2002), while sperm lacking both PH-20 and Hyal5 have not yet been studied.…”
Section: Status Of Sperm Acrosome In the Cumulus: The Controversymentioning
confidence: 97%
“…The most common application is in ophthalmic surgery, in which it is used in combination with local anesthetics. Some bacteria, such as Staphylococcus aureus, Streptococcus pyogenes et pneumoniae and Clostridium perfringens, produce hyaluronidase as a means of increasing mobility through the body's tissues and as an antigenic disguise that prevents their recognition by phagocytes of the immune system (Ponnuraj and Jedrzejas, 2000;Lin and Stern, 2001;Lokeshwar et al, 2002;Hajjaji et al, 2005;Kim et al, 2005;Girish and Kemparaju, 2006).…”
Section: Degradationmentioning
confidence: 99%
“…The abundance of HA in the ECM is regulated by the local-regional balance between HA synthase activity and degradation by membrane-associated and lysosomal hyaluronidases. PH20 is unique as a membrane-bound, neutral active enzyme with high specific activity toward HA in vitro and in vivo, which is capable of degrading matrix-associated megadalton HA polymers to small tetrasaccharide and hexasaccharide products (16)(17)(18)(19). Given the rapid endogenous turnover of HA, accumulation in tumors could involve disequilibrium between the enzymes that synthesize HA and the enzymes that catabolize HA or receptors for cellular uptake, which subsequently mediate intracellular metabolism (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%